El comunismo argentino y sus primeras relaciones con la revolución rusa y la Komintern: militancias locales, emigrados rusos y emisarios - Camarero, Hernán (El Colegio de México, A.C., 2023)
This article has two objectives. One is to examine the ways in which communism in Argentina used the October Revolution, the Soviet regime and the Comintern as references. The emergence of this political force is first reconstructed as a process of ideological-political redefinition that had a local imprint and that gave it peculiar characteristics. The other, more specifically, is to explore the labyrinthic early relationship of this current with the Comintern, an intimate, clandestine history. In the complex, changing and difficult ties between Buenos Aires and Moscow, a series of Russian emigres temporarily based in Río de la Plata played an important role, as did a later-renowned Argentine-German, the cadres of the International and, of course, the local party leaders.